Analysis of Consumers’ Preferences for Melon Using the Conjoint Method - Tiara Tannesha Hartono; Nafis Khuriyati; Ibnu Wahid Fakhrudin Aziz (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2022)
Melon (Cucumis melo L.) is a fruit widely known by the people of Indonesia, including Yogyakarta Province, which has several variants such as C. melo var reticulatus, C. melo var. inodorus, and C. melo var. catalupensis. These variants have different characteristics that can be distinguished by color, aroma, peel texture, as well as their respective markets. To find out consumers’ preferences for melon, the conjoint analysis method is used. The results showed that consumers in traditional retail preferred melons with small size, orange flesh, strong aroma, very sweet taste, slightly meshy peel texture, and crunchy flesh texture. Meanwhile, in modern retail, they prefer variants with a large size, green flesh, strong aroma, very sweet taste, non-meshy peel texture, and crunchy flesh texture. Sky Rocket, Glamor, Golden Langkawi, and Mai 119 variants are suitable for traditional and modern retail. There are also other suitable variants for traditional retail, namely Cantaloupe and Roc Melon, while Honey Globe and Action 434 are suitable for modern retail.